2016
DOI: 10.1007/s00702-016-1539-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term treatment of chronic migraine with OnabotulinumtoxinA: efficacy, quality of life and tolerability in a real-life setting

Abstract: Botulinum toxin was shown to be effective in treatment of chronic migraine. We wanted to explore its efficacy and tolerability in chronic application under real-life conditions. For this, 27 consecutive patients (age 45.6 ± 10.8 years, 25 females, 2 males) received altogether 176 injection series (IS) with 189.7 ± 45.8MU onabotulinumtoxinA (Botox(®)) according to the PREEMPT scheme. During the study period altogether 6.5 ± 2.9 (min 4, max 13) IS were applied per patient (total treatment time of 73.1 ± 36.9 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 53 publications
9
19
0
Order By: Relevance
“…During last years, studies considering long-term experience with Onabot A in a real-life setting have been published [10, 17, 18]. OnabotA efficacy showed consistency after first year; percentage of patients in which OnabotA response was not maintained after first year were among 10 and 15% comparing our results with a quite similar series as that by Cernuda-Morollon et al [10].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…During last years, studies considering long-term experience with Onabot A in a real-life setting have been published [10, 17, 18]. OnabotA efficacy showed consistency after first year; percentage of patients in which OnabotA response was not maintained after first year were among 10 and 15% comparing our results with a quite similar series as that by Cernuda-Morollon et al [10].…”
Section: Discussionsupporting
confidence: 81%
“…Another question still open to discussion is the possibility of ending OnabotA therapy after first year in patients with a good response; it has been shown that when treatment is stopped quality of life parameters worsen [17]. In the same way that previous studies [10, 18], we found that it is not easy to interrupt OnabotA therapy, even temporally. However, in nearly 20% of cases we were able to postpone OnabotA procedures to a fourth of fifth month.…”
Section: Discussionsupporting
confidence: 72%
“…Significant reduction in monthly headache frequency, headache severity, number of analgesics used and MIDAS scores in our cohort support the efficacy of OnabotA in reduction of the frequency, intensity, and duration of chronic migraines as well as decreasing medication overuse among CM patients who failed on traditional preventive therapies [22, 2527, 4244]. …”
Section: Discussionsupporting
confidence: 74%
“…Given the similar rates of medication overuse (76.2%) in our cohort at baseline, reduction in in number of analgesics used starting from the first injection and consistently throughout the study period emphasizes the potential role of OnabotA therapy in prevention of MOH via headache episode reduction [25, 42, 4850]. …”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation